Automatic Mapping of Business Process Models for Ontologies with an Associated Query System - Riehl Figueiredo, Lukas [UNESP]; Carvalho de Oliveira, Hilda [UNESP] (My University, 2019)
Business process models are employed in organizational environments to improve the understanding in the interactions between different sectors. They also help to better visualize the interdependencies from the processes that compose these environments. However, the understanding of these models is often limited to the visual representation of their elements. In addition, as the business process models become more complex, their readability and navigability are affected. It is difficult to represent and properly understand the implicit knowledge and the interdependencies of these models. The use of ontologies as a representation of business process models opens a complementary perspective to provide semantics to business processes. Ontologies conceptualize and organize the information that is embedded and unstructured in the business processes and that must be explored. They structure the implicit knowledge that is present in the business processes, enabling the understanding of this knowledge by machine. They also facilitate the sharing and reuse of knowledge by various agents, human or artificial. In this context, this work presents a systematic process to automatically map a business process model in BPMN v2.0 to an ontology, allowing to consult information about the model. To automate this systematic process, the PM2ONTO tool was developed, aiming to generate the ontology in OWL automatically, and made available predefined queries, elaborated with SPARQL, for querying information about the business process models.
Keywords: BPMN; Business process model; Documentation of business process model; Ontology; OWL; SPARQL; XPDL